Reproduction of Racial Inequality in Sinners (2025) - Raga Riswanda; Tenny Sudjatnika; Lili Awaludin (Journal of English Language and Education, 2026)
This study examines how Sinners (2025) dramatizes racial domination through the vampire genre by organizing inequality as a structural condition rather than an isolated act of prejudice. While current Black horror scholarship extensively analyzes metaphors of historical trauma, few studies examine the micro-sociological mechanics of capital extraction within these films. Addressing this gap, the film is selected because it places Black cultural space, especially music, communal gathering, and tradition at the center of conflict, allowing racial power to appear through both admiration and coercion. Using a qualitative film-text analysis, this research interprets key scenes through Pierre Bourdieu’s concepts of habitus, capital, and field. The findings show that racial inequality in Sinners operates through three interlocking mechanisms: (1) habitus as bodily recalibration and anticipatory restraint during intrusion, (2) capital as the capture and conversion of Black cultural gifts (especially musical talent) into resources for domination, and (3) field as spatial expansion and forced rule-change that collapses Black autonomy from within. Together, these mechanisms reveal racial reproduction as a repeated process sustained through symbolic legitimacy, highlighting how horror cinema can expose the everyday workings of racial hierarchy beneath the surface of inclusion.